A study of thalassaemia among blood donors in HUSM - Adam, Nor Atifah bt. Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Thalassaemia is a common autosomal recessive disorder and have a high incidence among people of Asian Indian origin, Southeast Asian and Northern Thailand. It is classified into a-thalassaemia and 13-thalassaemia. Thalassaemia is due to quantitative reductions in globin chains synthesis. Thalassaemia haemoglobinopathies are structural abnormalities of haemoglobin synthesis, where the synthesis of these haemoglobins are reduced in amount. To data, there is limited study on the effect of blood donation from a thalassaemia donor. So objectives of this study were to determine the prevalence and the type of thalassaemia among blood donors in Hospital Universiti Sains Malaysia (HUSM); and to use the data for future protocol in blood transfusion therapy. A total of 80 blood samples were obtained from the donors at the Transfusion Medical Unit, HUSM. 91.3% of donors were Malays, 1.3% was Chinese and 1.0% was Indian. The donors were selected according to the standard criteria. Thalassaemia screening was carried out using haemoglobin electrophoresis method. Hb A2 elution technique and quantitation of Hb F were performed. Most of the blood donors, 15% (n = 12) were diagnosed as thalassaemia 1 haemoglobinopathy. Out of that, 1 0 donors presented as microcytic hypochromic and 2 donors were normocytic normochromic.The type of thalassaemia were Hb E/ a-thalassaemia in 5 donors, Hb E trait in 3 donors, J3-thalassaemia in 3 donors and Hb E IJ3-thalassaemia in 1 donor. This findings were consistent to previous study or population study done by Vella (1962); Lie-injo & Duraisamy (1972); Ganesan et al (1976); showing that Hb E haemoglobinopathy is prevalence among Kelantan population. Screening test for thalassaemia trait is suggested to be included as the standard procedure of blood test before blood donation especially for the apheresis procedures. Further research is required to investigate the hypothesis that RBC from a donor with the thalassaemia will interfere with the purity of the platelet apheresis product.